Studying charm hadronisation into baryons with azimuthal correlations of Λ+c with charged particles in pp collisions at √𝑠 = 13 TeV: Letter - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Menzel, Marius; Nath, Abhishek; Reygers, Klaus; et al. (Physics letters, 2025)
The distribution of angular correlations between prompt charm hadrons and primary charged particles in pp collisions is sensitive to the charm-quark hadronisation process. In this letter, charm-baryon correlations are measured for the first time by studying the azimuthal-angle difference between charged particles and prompt Λc+ baryons produced in pp collisions at a centre-of-mass energy of s=13 TeV, with the ALICE detector. Λc+ baryons are reconstructed at midrapidity (|y|<0.5) in the transverse-momentum interval 3<pT<16 GeV/c, and correlated with charged particles with pT>0.3 GeV/c and pseudorapidity |η|<0.8. For 3<pTΛc+,D<5 GeV/c, the comparison with published measurements of D-meson and charged-particle correlations in the same collision system hints at a larger number of low-momentum particles associated with Λc+-baryon triggers than with D-meson triggers, both in the collinear and opposite directions with respect to the trigger particle. These differences can be quantified by the comparison of the properties of the near- and away-side correlation peaks, and are not reproduced by predictions of various Monte Carlo event generators, generally underpredicting the associated particle yields at pTassoc<1 GeV/c. This tension between Λc+-baryon and D-meson associated peak yields could suggest a modified fragmentation of the charm quark, or a different hadronisation process, when a charm baryon is produced in the final state.